FRI0387 Peripheral Neuropathy in Eosinophilic Granulomatosis with Polyangiitis (EGPA). Incat Disability Score To Evaluate Damage and To Predict Long Term Outcome in 50 Patients. (15th July 2016) - Padoan, R.; Felicetti, M.; Marconato, M.; Cinetto, F.; Agostini, C.; Punzi, L.; Schiavon, F.
Abstract : Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare necrotizing vasculitis characterized by bronchial asthma, hypereosinophilia and extrapulmonary granulomatous inflammation. One of the most frequently involved organ is the peripheral nervous system (PNS), followed by the lung and the skin. PNS involvement is usually characterized by mononeuritis multiplex or symmetrical peripheral neuropathy. Administration of corticosteroids and immunosuppressive agents typically achieves remission and results in good survival rates. However, patients may suffer from chronic residual functional deficits caused by neuropathy even after remission has been achieved. Although such deficits may disrupt the day-to-day functioning and quality of life, studies to target the residual neuropathy are still poor. Objectives: VDI can't precisely indentify the severity of peripheral neurologic damage, so we propose the INCAT (Inflammatory Neuropathy Cause and Treatment) disability score, to evaluate long term outcome and damage in this patients. Methods: We selected retrospectively patients affected by EGPA, satisfying ACR criteria, followed up by Rheumatology and Clinical Immunology Units, from 2005 through 2015. Basic demographic, duration of disease, clinical and serological features, treatments of each patient were routinely monitored at baseline, six, twelve months and last visit. Disease activity, relapses, damage and neurological involvement were also evaluated with Birmingham Vasculitis Activity Score (BVAS v3), Vasculitis Damage Index (VDI) and INCAT disability score. The INCAT score ranges from 0 (no signs of disability) to 10 (most severe disability). Statistical analyses were done using Mann Whitney test, Spearman correlation and Fisher's exact test. Results: 50 patients were included, middle aged (49.9±13.8 years), mainly women (31:19). Twentyfive patients (50%) presented with peripheral neurological involvement; this patients were older (56.3±13.4 yrs, p=0.0009) and mostly ANCA positive (48%, p=0.015). Patients who presented with an INCAT score ≥3, compared to those with a lower score, at baseline (52%, 13/25), had also at the end of follow up (6.3±3.8 yrs) a higher INCAT score (2.7±1.2, p<0.0001), higher VDI (2.70±1.48, p=0.0046) and mostly relapses with a peripheral neurological flare (46%, 6/13). These patients were also treated more frequently with cyclophosphamide (76.9%, p=0.034). In all patients INCAT score was also significantly correlated to VDI (p=0.0046), but not to BVAS. Conclusions: INCAT disability score measures daily activities limitation and it's used frequently as a primary end point in inflammatory polyneuropathy clinical trials. It's easy to administer and can be completed quickly, imposing a minimal burden on the administrator and the responder. It appears to be a valid tool, able to evaluate peripheral neurological damage, treatment response and to predict long term outcome. Further studies in a larger patients cohorts are needed. References: Hughes R. et al. Randomized Controlled Trial of Intravenous Immunoglobulin Versus Oral Prednisolone in Chronic Inflammatory Demyelinating Polyradiculoneuropathy. Ann Neurol 2001;50:195–201 Disclosure of Interest: None declared